Tomographic Volumetric Additive Manufacturing of Silicon Oxycarbide Ceramics. Issue 7 (27th January 2022) - Kollep, Max; Konstantinou, Georgia; Madrid-Wolff, Jorge; Boniface, Antoine; Hagelüken, Lorenz; Sasikumar, Pradeep Vallachira Warriam; Blugan, Gurdial; Delrot, Paul; Loterie, Damien; Brugger, Juergen; Moser, Christophe
Abstract : Ceramics are highly chemically, thermally, and mechanically resistant. These remarkable propertiers make them useful across multiple industries; but also, difficult to mold into complex shapes. A possibility to make convoluted ceramic parts is to use preceramic polymers (PCPs) in liquid form. The PCP resin is first solidified in a desired geometry and then transformed into ceramic compounds through a pyrolysis step that preserves the shape. Light‐based additive manufacturing (AM) is a promising route to achieve solidification of the PCP resin. Different approaches, such as stereolithography, have already been proposed but they all rely on a layer‐by‐layer printing process which limits printing speed and object geometry. Herein, the fabrication of complex 3D centimeter‐scale ceramic parts by using tomographic volumetric printing is presented, which is fast and offers a high‐resolution and geometrical design freedom. First, a photosensitive polysiloxane preceramic resin that is solidified by projecting light patterns from multiple angles is formulated. Then, the obtained 3D printed parts are converted into ceramics by pyrolysis. The strength of this approach is demonstrated through the fabrication of smooth, dense microcomponents exhibiting overhangs and hollow geometries without the need of supporting structures. Their resistance to thermal stress and harsh chemical treatments is characterized. Abstract : The fabrication of complex 3D centimeter‐scale ceramic parts by using tomographic volumetric additive manufacturing is presented. It is fast, exhibits high resolution (≈100 μm), and provides geometrical freedom. Polymerized green bodies are then pyrolyzed at 1000 °C to produce thermally and chemically resistant silicon oxycarbide ceramics.